E-Government Adoption in Developing Countries: A Systematic Review of Challenges and Opportunities - Aan Adiazmil. S; Eko Perdana (Public Studies and Business Administration Journal (PUSBA), 2024)
e-Government adoption in developing countries faces complex challenges influenced by technological, economic, social and cultural factors. This research aims to explore the role of government policy in encouraging and facilitating e-Government adoption in developing countries and identify critical obstacles that are often faced. The method used is a systematic literature review using the PRISMA framework. The research results show that effective government policies, technological support, economic investment, and increasing digital literacy are very important for the successful implementation of e-Government. This research has important implications for policy makers in formulating more effective strategies to support government digital transformation.